PEMANFAATAN LEARNING ANALYTICS SEBAGAI ALAT PENGAMBILAN KEPUTUSAN STRATEGIS DI SEKOLAH DASAR: PERAN KEPEMIMPINAN DIGITAL KEPALA SEKOLAH - Ninit Pujianti; Rahmi Saleh; Nurhizrah G; Rusdinal Rusdinal; Nellitawati Nellitawati (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
Every student activity—from diagnostic assessments and daily reflections to project assignments and interactions with learning videos—is recorded automatically and displayed graphically and with risk predictions via the PMM dashboard. The potential for this data to support strategic decision-making at the school level is significant, yet a national survey shows that most elementary schools still use this data solely for report card administration and reporting to the education office. This study explores the utilization of learning analytics from the Merdeka Mengajar Platform (PMM) as a strategic decision-making tool in elementary schools, focusing on the role of the principal's digital leadership. Using a qualitative case study method, data were collected through interviews (n=10), PMM dashboard analysis, and three-month observation at SD Negeri 21 Simpang Rumbio, Kota Solok, West Sumatra (July–September 2025). Findings reveal five key applications: early risk identification, differentiated learning groups, flexible scheduling, teacher development, and parent reporting. The principal's digital leadership increased utilization from 24 % (2023) to 89 % (2025) through vision, infrastructure, and data culture. This contributes practical insights for basic education in developing countries, recommending principal training and data literacy programs.